A Case of Delayed Myelopathy Caused by Atlantoaxial Subluxation without Fracture. (2nd April 2013) - Takamatsu, Ryo; Takahashi, Hiroshi; Yokoyama, Yuichiro; Terajima, Fumiaki; Inoue, Yasuhiro; Fukutake, Katsunori; Wada, Akihito
Abstract : We report a case of delayed myelopathy caused by atlantoaxial subluxation without fracture. The patient was a 38-year-old male who became aware of weakness in extremities. The patient had a history of hitting his head severely while diving into a swimming pool at the age of 14 years old. At that time, cervical spine plain X-ray images showed no fracture, and the cervical pain disappeared after use of a collar for several weeks. At his first visit to our department, X-ray images showed an unstable atlantoaxial joint. After surgery, weakness of the extremities gradually improved. At 6 months after surgery, bone union was completed and the symptoms disappeared. This case shows that atlantoaxial ligament injuries are difficult to diagnose and may easily be missed. A high level of suspicion is important in such cases, since neurological compromise or deterioration may occur many years after the injury.